Книготорговельна діяльність церковних православних братств Волинської губернії в другій половині ХІХ – на початку ХХ ст. - Сажок, Оксана; Sazhok, Oksana (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті розглянуто ведення книжкової торгівлі церковними православними братствами Волинської губернії в другій половині ХІХ – на початку ХХ ст. Відзначено життєспроможність братських книгарень, з’ясовано основні причини закриття деяких із них. Розкрито культурно-освітню роль цих братських інституцій на Волині. The article deals with the book trade of ecclesiastical Orthodox fraternities of Volyn province in the second half of the nineteenth and early twentieth century. The potentialities of fraternal bookshops are shown, the motives that led to their establishment are set and the preconditions for closing some of them are indicated. The cultural and educational role and importance of these fraternal establishments for the Volyn region are clarified; their interrelation with other fraternal educational institutions is tracked. The contribution of church fraternities to the dissemination of local knowledge is noted. The sources of supply of bookshelves of fraternities with new literature are revealed. The assortment of printed products in fraternal bookstores is characterized. The names of the responsible persons for this direction of fraternal activity, as well as individuals involved in its development, were identified. A selective comparative characteristic of the most significant indicators of the bookselling of a particular fraternity functioning in the territory of the Volyn diocese during the indicated period is given.
Bookselling Activity of Ecclesiastical Orthodox Fraternities of the Volyn Province in the Second Half of the Nineteenth and Early Twentieth Centuries
Keywords: Волинська губернія; церковні православні братства; книжкова торгівля; друкована продукція; Volyn province; ecclesiastical Orthodox fraternities; book-trade; printed production